Further education, professional and occupational pedagogy : knowledge and experiences - Loo, Sai (Routledge, 2019)
"The further education (and skills) sector in England has been viewed as a backwater of educational research compared to the other sectors. This comparative lack of research and related publications may be due in part to the huge diversity of the sector. Further Education, Professional and Occupational Pedagogy addresses some of the gaps by bringing together empirical research and theoretical frameworks to give a coherent understanding of the sector, emphasising the occupational experiences of deliverers, alongside their pedagogic and life experiences. This book also includes investigations on the education of professionals in the higher education sector"- Resumé vydavatele
Keywords: vzdělávání dospělých -- Velká Británie; učitelé -- Velká Británie; další vzdělávání -- Velká Británie; adult learning -- Great Britain; teachers -- Great Britain; continuing education -- Great Britain; elektronické knihy; monografie; electronic books; monographs